Secular trends in adult and child anthropometry in four Guatemalan villages - Ruel, Marie T.; Rivera, Juan A.; Castro, Hilda; Habicht, Jean-Pierre; Martorell, Reynaldo (SAGE Publications, 1992)
Secular trends in the stature and head circumference of adults born between 1905 and 1959 and in the length of three-year-old children born between 1965 and 1985 from four villages of eastern Guatemala are analysed. Data were collected before (1968), during (1969–1977), and after (1988) a longitudinal protein-energy supplementation trial conducted in the four villages. No secular trends are observed in the age-adjusted height or the head circumference of the adults studied; similar results are obtained whether a longitudinal or a cross-sectional method is used to correct height for the effects of ageing. A positive and significant linear trend is observed in the length of the three-year-olds. The estimated increase of 2.5–3.3 cm seen over this 20-year period represents only approximately 27% of the total deficit in length seen in these children in 1968 (11 cm).